CTnI electrochemical detection kit based on nanometer material and SI-RAFT, use method and application
By using nanomaterials to modify the electrodes in the electrochemical detection kit and combining the SI-RAFT polymerization signal amplification strategy, the existing cTnI detection methods are solved, and high sensitivity, low detection limit and easy operation are achieved. Detection effect.
Patent Information
- Application Number
- CN202411616953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing cardiac troponin I (cTnI) detection methods have limitations such as long time, low sensitivity, high cost, and many sample processing steps, and it is difficult to meet the needs of fast, sensitive and efficient detection.
Using the reversible addition-break chain transfer (SI-RAFT) polymerization signal amplification strategy based on nanomaterials (MoS2/CuS-Au) and surface-induced reversible addition-break chain transfer (SI-RAFT) polymer, an electrochemical detection kit was constructed by modifying the electrode surface and utilizing SI-RAFT polymer. Grafting is used to amplify the signal to achieve high sensitivity detection of cTnI.
The sensitivity and selectivity of detecting cTnI are significantly improved, with the detection limit as low as 10.83fg·mL-1, and it is simple to operate and low cost. It is suitable for human serum detection and has good applicability and stability.
Smart Images

Figure CN119470915A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrochemical detection kit for detecting cardiac troponin I (cTnI) constructed based on nanomaterials (MoS2 / CuS-Au) and a surface-initiated reversible addition-fragmentation chain transfer (SI-RAFT) polymerization signal amplification strategy, a use method and an application, and belongs to the technical field of bioanalysis. Background Art
[0002] Acute myocardial infarction (AMI) is a disease that seriously threatens human life and health and is the main cause of death from cardiovascular diseases. Since cardiac troponin I (cTnI) only exists in myocardial cells, and the concentration of cTnI will increase rapidly only when myocardial cells are damaged. Clinically, cTnI is often used as the gold standard for diagnosing acute myocardial infarction. Therefore, it is of great application value to construct a simple, fast and sensitive cTnI detection method.
[0003] In recent years, a variety of methods for detecting cTnI have been developed, such as enzyme-linked immunosorbent assay, chemiluminescent immunoassay, fluorescent immunoassay, and electrochemical sensing. At present, enzyme-linked immunosorbent assay is still the most commonly used method for clinical analysis of cTnI. However, this method still has limitations such as long time consumption, low sensitivity, high cost, and many sample processing steps, which restrict its further application. In contrast, electrochemical sensors have attracted widespread attention due to their fast response speed, low cost, simple operation, and easy miniaturization.
[0004] The method of improving the sensitivity of sensors by modifying the electrode surface with materials with large specific surface area, good conductivity and high chemical stability has been widely used, but its sensitivity, selectivity, stability and other properties need to be further improved. In this study, the trimetallic composite material composed of molybdenum disulfide (MoS2), copper sulfide (CuS) and gold (Au) was modified on the electrode surface, which will greatly improve the bioloading capacity, conductivity and biocompatibility of the sensor. In order to further improve the detection sensitivity of the sensor, the surface-initiated reversible addition-fragmentation chain transfer polymerization (SI-RAFT) with controllable reaction and extensive reactive monomers was applied to the sensing field for rapid, sensitive and highly specific detection of acute myocardial infarction biomarker cTnI. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an electrochemical detection kit for detecting cTnI based on nanomaterials (MoS2 / CuS-Au) and surface-initiated reversible addition-fragmentation chain transfer (SI-RAFT) polymerization signal amplification strategy, a method of use and application, which has the advantages of strong selectivity, high sensitivity, good stability, etc., and has good applicability in human serum detection.
[0006] In order to achieve the above-mentioned purpose, the technical solution of the present invention is, on the one hand, to provide a cTnI electrochemical detection kit based on MoS2 / CuS-Au nanomaterials and SI-RAFT, comprising the following raw materials: GCE, MoS2 / CuS-Au, Apt1, MCH, Apt2-CPAD solution, SI-RAFT solution, silver ammonia solution, ultrapure water, anhydrous ethanol, PBS buffer and KCl.
[0007] Further, the preparation method of Apt2-CPAD solution is:
[0008] 100 μL of 4 mM EDC solution and 100 μL of 1 mM NHS solution were evenly mixed and shaken at 37°C for 3 h; then, 100 μL of 2 mM chain transfer agent CPAD solution was added and the shaking was continued for 3 h to fully activate the carboxyl group in CPAD; subsequently, 100 μL of 2 mM Apt2 solution with amino groups was added and the shaking was continued for 3 h to obtain Apt2-CPAD bioconjugation solution, which was stored at 4°C for future use.
[0009] Further, the preparation method of SI-RAFT solution is:
[0010] 20 μL of 50 μM VA-044 solution and 40 μL of 0.8-2.0 mM C 10 H 14 The O solution was added into 340 μL of 25% DMF solution and stirred evenly to prepare a SI-RAFT solution.
[0011] On the other hand, the technical solution of the present invention is to provide a method for using the cTnI electrochemical detection kit, comprising the following steps:
[0012] (1) Electrode modification
[0013] ① Drop the MoS2 / CuS-Au solution on the treated GCE surface for reaction;
[0014] ② Drop the Apt1 solution onto the GCE surface of step ① to react;
[0015] ③ Immerse the GCE in step ② in the MCH solution for reaction;
[0016] ④ Drop the solution to be tested on the GCE surface of step ③ for reaction;
[0017] ⑤ Drop the Apt2-CPAD solution onto the GCE surface of step ④ to react;
[0018] ⑥ Immersing the GCE in step ⑤ in a SI-RAFT solution for reaction;
[0019] ⑦ Immerse the GCE in step ⑥ in a silver ammonia solution for reaction;
[0020] (2) Electrochemical determination
[0021] The modified electrode was immersed in KCl solution, and the dissolution peak current of AgNPs on the electrode surface was recorded by SWV method. The target cTnI in the detection solution was quantitatively analyzed according to the current intensity.
[0022] Further, the reaction temperature of step ① is 37°C, and the time is 3h; the reaction temperature of step ② is 37°C, and the time is 1.5h; the reaction temperature of step ③ is 37°C, and the time is 0.5h; the reaction temperature of step ④ is 37°C, and the time is 1h; the reaction temperature of step ⑤ is 37°C, and the time is 1h; the reaction temperature of step ⑥ is 47°C, and the time is 1.5h; the reaction temperature of step ⑦ is 37°C, and the time is 1h.
[0023] Furthermore, the detection conditions of the SWV method are: potential range: -0.2 to 0.1 V, potential amplitude: 0.025 V, potential increment: 4 mV, and resting time: 30 s.
[0024] On the other hand, the technical solution of the present invention is to provide a use of the cTnI electrochemical detection kit in the preparation of a cTnI detection product.
[0025] The construction process of the kit of the present invention is shown in FIG1 .
[0026] First, the substrate material (MoS2 / CuS-Au) is modified onto the GCE electrode by electrostatic adsorption. Then, Apt1 is connected to the electrode surface through the Au-S bond, and then the unreacted binding sites are blocked with MCH. Subsequently, Apt1 specifically recognizes and captures the target cTnI. The target cTnI then further specifically recognizes Apt2 on Apt2-CPAD to form a sandwich structure. Next, the electrode is immersed in a SI-RAFT solution to graft a large number of monomers with aldehyde groups onto the electrode. Finally, the modified electrode is immersed in a silver ammonia solution, and the reducing aldehyde groups can remove the Ag in the solution. + The AgNPs were reduced to AgNPs and deposited in situ on the electrode surface. The modified electrode was immersed in potassium chloride electrolyte and its detection performance was tested by square wave voltammetry (SWV).
[0027] Beneficial Effects of the Invention
[0028] 1. The present invention uses the nanomaterial MoS2 / CuS-Au with large specific surface area and good conductivity, which provides more active sites for the subsequent connection of signal units, thereby significantly improving the sensitivity of the sensing system.
[0029] 2. The present invention adopts SI-RAFT polymerization signal amplification strategy, which is a simple, rapid and efficient polymer synthesis method with controllable reaction, wide applicable monomers, and the ability to synthesize polymers with clear structure, low dispersibility and controllable molecular weight. At the same time, this method can avoid the high cost of natural enzymes and the environmental pollution caused by transition metal catalysts.
[0030] 3. The present invention uses nanomaterials (MoS2 / CuS-Au) as the substrate material. Apt1 is autonomously mounted on the electrode through the Au-S bond, specifically identifying and capturing cTnI. Subsequently, Apt2 on Apt2-CPAD is specifically connected to cTnI to form a sandwich structure of Apt1-cTnI-Apt2. Subsequently, a large number of monomers with aldehyde groups are grafted onto the electrode through SI-RAFT polymerization. Then, Ag is transferred to the electrode with the help of silver ammonia solution. + The AgNPs were reduced to AgNPs and deposited in situ on the electrode surface. Finally, the square wave voltammetry (SWV) was used to record the response value of the oxidation current to achieve high-sensitivity detection of the target. Under the optimal conditions, the current intensity and the logarithm of the cTnI concentration showed a good linear relationship, and the linear equation was: I (μA) = 8.27log [C cTnI / ng·mL -1 ]+43.77(R 2 =0.998), the detection limit is as low as 10.83 fg·mL -1 The experimental results show that the present invention has good selectivity and stability, simple operation and low cost, and is expected to be extended to the detection of other targets and clinical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] FIG1 is a schematic diagram of the kit construction process (A) and a schematic diagram of the SI-RAFT principle (B).
[0032] Figure 2 There is no MoS2 / CuS-Au (curve a), Apt1 (curve b), cTnI (curve c), Apt2 (curve d), CPAD (curve e), C 10 H 14 SWV curves modified by O (curve f), VA-044 (curve g), SMR (curve h) and experimental group (curve i).
[0033] Figure 3 A is a mixture containing 0.1M KNO3 and 5mM [Fe(CN)6] 3- / 4- EIS curves of GCE at different stages in solution. Figure 3 B is a solution containing 0.1M KNO3 and 5mM [Fe(CN)6] 3- / 4- CV curves of GCE at different stages in the solution.
[0034] Figure 4 A and 4B are TEM and UV absorption images of AuNPs. Figure 4 C is the SEM image of MoS2. Figure 4 D is the SEM image of CuS. Figure 4 E and 4F are SEM images of MoS2 / CuS. Figure 4 G is the TEM image of MoS2 / CuS. Figure 4 H is the TEM image of MoS2 / CuS-Au. Figure 4 I is the HRTEM image of MoS2 / CuS-Au.
[0035] Figure 5 A is the optimized condition of substrate material concentration. Figure 5 B is the optimization of monomer concentration conditions for SI-RAFT reaction. Figure 5 C is the optimized conditions for the silver mirror reaction time. Figure 5 D is the optimized condition of silver ammonia solution concentration.
[0036] Figure 6 A is a schematic diagram of the current signal intensity obtained by detecting different concentrations of cTnI. Figure 6 B is the linear relationship between the current signal intensity and different concentrations of cTnI.
[0037] Figure 7 A is the selectivity study for different antigens (DR1, HER2, ERα, ERβ and blank group). Figure 7 B is 1 pg·mL in PBS buffer, 10% (v / v) normal human serum and 20% (v / v) normal human serum. -1 , 100pg·mL -1 , 10ng·mL -1 The current response of cTnI was studied to investigate its anti-interference ability. Figure 7 C is to study its reproducibility by measuring within-group and between-group. Figure 7 D is the change of current with time after being placed for a period of time, and its stability is studied. DETAILED DESCRIPTION
[0038] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.
[0039] cTnI antigen was provided by Shanghai Lingchao Biotechnology Co., Ltd. cTnI aptamer (Apt1) and cTnI aptamer 2 (Apt2) were synthesized by Sangon Biotechnology (Shanghai) Co., Ltd.
[0040] The sequence of Apt1 is:
[0041] 5'-SH-(CH2)6-CGTGCAGTACGCCAACCTTTCTCATGCGCTGCCCCTCTTA-3' (SEQ ID NO. 1).
[0042] The sequence of Apt2 is:
[0043] 5'-NH2-(CH2)6-CGCATGCCAAACGTTGCCTCATAGTTCCCTCCCCGTGTCC-3' (SEQ ID NO. 2).
[0044] Example 1: Preparation of materials
[0045] (1) Synthesis of AuNPs
[0046] First, 50 mL of ultrapure water and 1.5 mL of 1% HAuCl4 solution were added to a 100 mL round-bottom flask in sequence, heated in an oil bath and stirred vigorously. After the solution boiled, trisodium citrate dihydrate aqueous solution (10.5 mL, 38.8 mM) was quickly added, and boiling was continued until the color of the solution no longer changed (the color of the solution gradually changed from light yellow to light purple, and finally to purple red), and heating and stirring were continued for 15 min. Then, the heat source was removed, stirred in the dark to room temperature, and the AuNPs solution was obtained, which was refrigerated at 4 ° C in the dark.
[0047] (2) Preparation of MoS2 / CuS-Au
[0048] First, ammonium molybdate tetrahydrate (0.5 g) was slowly added to 30 mL ultrapure water and stirred vigorously for 30 min. Then, copper nitrate trihydrate (0.3 g) and thioacetamide (0.35 g) were added in sequence and continued to stir vigorously for 1 h. Subsequently, the entire mixed system was ultrasonically dispersed for 60 min to make the solution uniformly dispersed. The mixed solution was then quickly transferred to a 50 mL PTFE autoclave and reacted at 200 ° C for 24 h. After naturally cooling to room temperature, ultrapure water and anhydrous ethanol were centrifuged and washed in sequence until the pH value reached neutral. Then, the obtained black powder MoS2 / CuS was dried in a 50 ° C oven for 10 h. Finally, the prepared MoS2 / CuS was dispersed in the AuNPs solution and ultrasonically dispersed for 1 h in the dark to obtain a uniformly dispersed MoS2 / CuS-Au nanocomposite.
[0049] (3) Preparation of Apt2-CPAD
[0050] First, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) solution (100 μL, 4 mM) and N-hydroxysuccinimide (NHS) solution (100 μL, 1 mM) were evenly mixed and vigorously shaken on a 37°C shaker for 3 h. Then, a chain transfer agent 4-cyano-4-(phenylcarbonylthio) valeric acid (CPAD) solution (100 μL, 2 mM) was added and continued to be vigorously shaken on a shaker for 3 h to fully activate the carboxyl group in CPAD. Subsequently, an Apt2 solution with an amino group (100 μL, 2 mM) was added and continued to be shaken on a shaker with the activated CPAD for 3 h. Finally, an Apt2-CPAD bioconjugated solution was obtained and stored at 4°C for use.
[0051] (4) Preparation of SI-RAFT solution
[0052] 20 μL of azobisisobutylimidazoline hydrochloride (VA-044) solution (50 μM) and 40 μL of perillaldehyde (C 10 H 14 O) solution (0.8-2.0 mM) was added into 340 μL of 25% (v / v) N,N-dimethylformamide (DMF) solution and stirred evenly to prepare a SI-RAFT solution.
[0053] Example 2: Kit
[0054] A cTnI electrochemical detection kit based on MoS2 / CuS-Au nanomaterials and surface-initiated reversible addition-fragmentation chain transfer polymerization (SI-RAFT) signal amplification strategy comprises the following raw materials: glassy carbon electrode (GCE), MoS2 / CuS-Au, Apt1, 6-mercapto-1-hexanol (MCH), Apt2-CPAD solution, SI-RAFT solution, silver ammonia solution, ultrapure water, anhydrous ethanol, PBS buffer and KCl.
[0055] Example 3: Detection method of the kit
[0056] (1) Electrode pretreatment
[0057] The surface of the glassy carbon electrode (GCE) was first polished with 0.3 μm alumina powder, and then the electrode was ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water in sequence. 4- / 3- The electrode was detected by cyclic voltammetry (CV) in a 0.2 M KNO3 solution until the potential difference of the bare electrode was less than 75 mV. Finally, the electrode was ultrasonically cleaned with anhydrous ethanol and ultrapure water.
[0058] (2) Modified electrode
[0059] ① 8 μL MoS2 / CuS-Au solution (0.3~2.1 mg·mL -1 ) was dropped on the pretreated GCE surface and reacted in an oven at 37 °C for 3 h;
[0060] ② Drop 10 μL of Apt1 solution (1 μM) onto the GCE surface of step ①, react in a 37°C oven for 1.5 h, wash with PBS buffer, and blow dry with N2;
[0061] ③ Immerse the GCE prepared in step ② in 200 μL MCH solution (2 mM), react in a 37°C oven for 0.5 h, wash with 60% (v / v) ethanol solution, and blow dry with N2;
[0062] ④ Drop 10 μL of the solution to be tested (or containing cTnI antigen) on the GCE surface of step ③, react in a 37°C oven for 1 h, wash with PBS buffer, and blow dry with N2;
[0063] ⑤ Drop 10 μL of Apt2-CPAD solution (1 μM) on the GCE surface of step ④, react in a 37°C oven for 1 h, wash with PBS buffer, and blow dry with N2;
[0064] ⑥ Immerse the GCE from step ⑤ in 200 μL SI-RAFT solution, react in a 47°C oven for 1.5 h, wash with 25% (v / v) DMF solution, and blow dry with N2;
[0065] ⑦ Immerse the GCE from step ⑥ in 200 μL silver ammonia solution (SMR) (0.1 mM to 0.6 mM), react in an oven at 37 °C for 1 h (in situ metallization), wash with ultrapure water, and blow dry with N2;
[0066] (3) Electrochemical determination
[0067] The modified electrode was immersed in 1M KCl solution, and the dissolution peak current of AgNPs on the electrode surface was recorded by SWV method. The target cTnI was quantitatively analyzed according to the current intensity (potential range: -0.2~0.1V, potential amplitude: 0.025V, potential increment: 4mV, static time: 30s).
[0068] Example 4: Feasibility Verification
[0069] In order to evaluate the feasibility of the kit of the present invention for determining cTnI, the current responses of the different modified electrodes were compared by SWV. Figure 2 As shown, in the process of electrode modification, in the absence of MoS2 / CuS-Au (curve a), Apt1 (curve b), cTnI (curve c), Apt2 (curve d), CPAD (curve e), monomer C 10 H 14In the cases of O (curve f), VA-044 (curve g) and SMR (curve h), no obvious current signal was observed. This is because when any one of the materials is missing, the subsequent materials cannot be fixed on the electrode surface, resulting in the inability to proceed with subsequent reactions. However, an obvious peak current (curve i) was observed at -0.012V for the electrode modified by the complete step. The above results confirm the feasibility of this sensing system for cTnI detection.
[0070] Example 5: Characterization
[0071] Electrochemical impedance spectroscopy (EIS) is very sensitive to subtle changes in the electrode surface, so we used this method to characterize the construction process of the electrochemical aptamer sensing system. In the Nyquist plot, the diameter of the semicircle in the high-frequency region is equal to the charge transfer impedance (Rct) between the electrolyte and the electrode surface. Figure 3 As shown in Figure A, the charge transfer resistance (Rct) of the bare electrode is 252.19Ω (curve a). When MoS2 / CuS-Au is modified on the electrode surface, the impedance value decreases due to its increased conductivity (~142.18Ω, curve b). When Apt1 is attached to the electrode surface, the charge transfer rate is hindered due to the increased steric hindrance formed on the surface monolayer, and Rct increases to 466.91Ω (curve c). After blocking with MCH, the steric hindrance is further increased, and Rct increases to 744.5Ω (curve d). When cTnI specifically binds to the aptamer, the impedance value increases further, indicating that the non-conductive bioactive substance is successfully modified to the electrode surface (~1026.4Ω, curve e). When Apt2-CPAD is modified to the electrode through specific recognition, the impedance value increases to 1333.6Ω (curve f). After the SI-RAFT reaction, a large number of hydrophobic monomers are modified to the electrode surface, resulting in a significant increase in the impedance value (~2329Ω, curve g). Finally, after AgNPs were in situ deposited on the electrode surface, the impedance value dropped significantly to 863.47Ω (curve h), indicating that there were abundant electroactive substances on the electrode surface. The above experimental results show that the construction of the electrochemical aptamer sensing system is successful. At the same time, the electrochemical characterization of the gradually modified electrodes was further carried out using cyclic voltammetry (CV). As shown in Figure 3B, different modified electrodes showed completely different peak currents, and the results were the same as the EIS change trend. This result further illustrates the successful preparation of the sensing system.
[0072] The morphology and size of AuNPs were characterized by transmission electron microscopy. Figure 4 A shows that AuNPs are uniformly dispersed spherical with a particle size of about 20 nm. Figure 4As shown in B, the UV-visible absorption spectrum of AuNPs shows the characteristic absorption peak of AuNPs at 520nm, proving the successful preparation of AuNPs. Figure 4 C), CuS( Figure 4 D) and MoS2 / CuS( Figure 4 E and Figure 4 F) was characterized. As can be seen from the figure, MoS2 with folded edges is compounded with layered CuS to form MoS2 / CuS with a flower-like layered structure. The flower-like layered structure of MoS2 / CuS provides a large specific surface area for the loading of gold nanoparticles, thereby improving the sensitivity of the sensing system. Figure 4 G and Figure 4 H are TEM images of MoS2 / CuS and MoS2 / CuS-Au respectively. From the figure, we can see that a large number of nanoparticles with uniform size are loaded on the surface of MoS2 / CuS. From the HRTEM image ( Figure 4 In I), it can be seen that the gold nanoparticles on MoS2 / CuS-Au are approximately 20 nm.
[0073] Example 6: Optimization of detection conditions
[0074] In order to achieve the best performance of the sensing system, key parameters such as the concentration of MoS2 / CuS-Au substrate material, SI-RAFT reaction monomer concentration, in situ metallization time, and silver ammonia solution concentration were optimized.
[0075] (1) Optimization of MoS2 / CuS-Au substrate material concentration
[0076] First, the effect of substrate material concentration on the current response of the sensing system was studied. Figure 5 As shown in A, when other conditions remain unchanged, 0.3~1.5mg·mL -1 The current intensity increases with the increase of substrate material concentration. However, when the substrate material concentration continues to increase, the current intensity decreases. This may be due to the fact that the conductive layer is too thick, which affects the electron transfer on the electrode surface. Therefore, the optimal substrate material concentration is 1.5 mg mL -1 .
[0077] (2) Optimization of monomer concentration in SI-RAFT reaction
[0078] We studied the effect of monomeric perillaldehyde concentration on SI-RAFT reaction in the range of 0.8 to 2.0 mM. Figure 5As shown in Figure B, when other conditions remain unchanged, the monomer concentration is in the range of 0.8 to 1.6 mM, and the current intensity increases with the increase of monomer concentration. When the monomer concentration continues to increase, the current intensity decreases. Therefore, the optimal monomer concentration for SI-RAFT reaction is 1.6 mM.
[0079] (3) In-situ metallization time
[0080] from Figure 5 It can be seen from Figure C that, when other conditions remain unchanged, the current intensity increases significantly with the increase of in-situ metallization time from 20 to 60 minutes, and the peak current tends to be stable after 60 minutes. Therefore, 60 minutes is selected as the optimal reaction time for in-situ metallization.
[0081] (4) Silver ammonia solution concentration
[0082] like Figure 5 As shown in Figure D, when other conditions remain unchanged, within the range of 0.1 to 0.4 mM, as the concentration of silver ammonia solution increases, the current intensity increases sharply, and after 0.4 mM, the current intensity tends to be stable. Therefore, 0.4 mM is selected as the optimal reaction concentration for in-situ metallization.
[0083] Example 7: Performance Analysis
[0084] Under the optimal conditions of Example 6, the SWV response signal value of the modified glassy carbon electrode was recorded in 1M KCl solution to study the detection range and detection limit of this strategy. Figure 6 As shown, at 1pg·mL -1 ~1 μg mL -1 Within the range, the SWV peak current and the logarithm of the cTnI concentration showed a good linear relationship. The linear regression equation was: I (μA) = 8.27log [C cTnI / ng·mL -1 ]+43.77(R 2 =0.998), detection limit: 10.83 fg·mL -1 Compared with several other methods (Table 1), the method for detecting cTnI proposed in the present invention has a wider detection range, a lower detection limit, and high sensitivity. This indicates that the kit has potential application value in the early detection of acute myocardial infarction.
[0085] Table 1 Comparison of the kit of the present invention with several other cTnI detection methods
[0086]
[0087] Example 8: Selectivity, anti-interference ability, reproducibility and stability of the kit
[0088] In order to verify the selectivity of the sensing system for different proteins, DR1, HER2, ERα, and ERβ (1 ng mL -1 ) and compared with cTnI (1 ng mL -1 ) were compared. The results are shown in Figure 7 As shown in A, the peak current of cTnI is significantly higher than that of other proteins. This is because only the target cTnI can specifically bind to the cTnI aptamer, while proteins from other sources are difficult to be specifically recognized and captured, so there is only a small non-specific signal value. This result shows that the aptamer sensing system has a high selectivity for cTnI. In order to evaluate the anti-interference ability of the aptamer sensing system, the concentration of 1pg mL was measured in 0.1M PBS buffer, 10% (v / v) and 20% (v / v) normal human serum. -1 , 100pg·mL -1 and 10ng·mL -1 The current signal of the cTnI sample. Figure 7 As shown in B, the peak current of the 10% (v / v) serum sample was 98.09% (1 pg mL -1 )、98.97%(100pg·mL -1 )、98.74%(10ng·mL -1 The peak current of the 20% (v / v) serum sample was 96.78% of that of the PBS buffer (1 pg·mL -1 )、98.05%(100pg·mL -1 )、96.84%(10ng·mL -1 ). Therefore, the aptamer sensing system has strong anti-interference ability. In addition, the reproducibility of the prepared aptamer sensing system was studied by measuring the intra-group and inter-group. Figure 7 As shown in Figure C, the relative standard deviations (RSDs) within and between groups were 2.06% and 2.59%, respectively, indicating that the constructed aptamer sensing electrode has good reproducibility. In order to evaluate the stability of the constructed aptamer sensing system, the prepared electrodes were dried and sealed and stored at 4°C for 1, 3, 5, 7 and 14 days. Figure 7 As shown in D, when the cTnI concentration is 1 ng·mL -1 The current signal values were maintained at 99.68%, 98.83%, 97.03%, 94.66% and 91.55% of the initial current within 14 days, respectively, indicating that the aptamer sensing system has good stability.
[0089] Example 9: Practical application value
[0090] In order to evaluate the actual clinical value of this method, we measured the cTnI concentration in the serum of 6 AMI patients. It is worth noting that the serum of some patients was diluted to an appropriate concentration. The results of the determination by this method are shown in Table 2. The relative error was -3.22% to 4.17%, and the RSD was less than 5%. This result proves the applicability of the sensing system in actual clinical testing. These good application performances are essential for providing accurate and reliable diagnostic results, and are expected to make it an effective tool for early detection of AMI.
[0091] Table 2 Comparison of this method with clinical results
[0092]
Claims
1. A cTnI electrochemical detection kit based on MoS2 / CuS-Au nanomaterials and SI-RAFT, characterized in that: The invention comprises the following raw materials: GCE, MoS2 / CuS-Au, Apt1, MCH, Apt2-CPAD solution, SI-RAFT solution and silver ammonia solution.
2. The cTnI electrochemical detection kit according to claim 1, characterized in that: Ultrapure water, anhydrous ethanol, PBS buffer and KCl are also included.
3. The cTnI electrochemical detection kit according to claim 1, characterized in that: The sequence of Apt1 is shown as SEQ ID NO.
1.
4. The cTnI electrochemical detection kit according to claim 1, characterized in that: The preparation method of Apt2-CPAD solution is: 100 μL of 4 mM EDC solution and 100 μL of 1 mM NHS solution were evenly mixed and shaken at 37°C for 3 h; then, 100 μL of 2 mM chain transfer agent CPAD solution was added and the shaking was continued for 3 h to fully activate the carboxyl group in CPAD; subsequently, 100 μL of 2 mM Apt2 solution with amino groups was added and the shaking was continued for 3 h to obtain Apt2-CPAD bioconjugation solution, which was stored at 4°C for future use.
5. The cTnI electrochemical detection kit according to claim 4, characterized in that: The Apt2 sequence is shown as SEQ ID NO.
2.
6. The cTnI electrochemical detection kit according to claim 1, characterized in that: The preparation method of SI-RAFT solution is: 20 μL of 50 μM VA-044 solution and 40 μL of 0.8-2.0 mM C 10 H 14 The O solution was added into 340 μL of 25% DMF solution and stirred evenly to prepare a SI-RAFT solution.
7. A method for using the cTnI electrochemical detection kit according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Electrode modification ① Drop the MoS2 / CuS-Au solution on the treated GCE surface for reaction; ② Drop the Apt1 solution onto the GCE surface of step ① to react; ③ Immerse the GCE in step ② in the MCH solution for reaction; ④ Drop the solution to be tested on the GCE surface of step ③ for reaction; ⑤ Drop the Apt2-CPAD solution onto the GCE surface of step ④ to react; ⑥ Immersing the GCE in step ⑤ in a SI-RAFT solution for reaction; ⑦ Immerse the GCE in step ⑥ in a silver ammonia solution for reaction; (2) Electrochemical determination The modified electrode was immersed in KCl solution, and the dissolution peak current of AgNPs on the electrode surface was recorded by SWV method. The target cTnI in the detection solution was quantitatively analyzed according to the current intensity.
8. The method of use according to claim 7, characterized in that: The reaction temperature of step ① is 37°C, and the time is 3h; the reaction temperature of step ② is 37°C, and the time is 1.5h; the reaction temperature of step ③ is 37°C, and the time is 0.5h; the reaction temperature of step ④ is 37°C, and the time is 1h; the reaction temperature of step ⑤ is 37°C, and the time is 1h; the reaction temperature of step ⑥ is 47°C, and the time is 1.5h; the reaction temperature of step ⑦ is 37°C, and the time is 1h.
9. The method of use according to claim 7, characterized in that: The detection conditions of the SWV method are: potential range: -0.2 to 0.1 V, potential amplitude: 0.025 V, potential increment: 4 mV, and static time: 30 s.
10. Use of the cTnI electrochemical detection kit according to any one of claims 1 to 6 in the preparation of a product for detecting cTnI.